Analisis Bibliometrik (2012-2023): Penyebab Penyakit Marasmus Yang Terjadi Pada Anak Usia Dini - Agis Tiara; Anisa Pratama; Miftha Khaeronnisa; Syahla Magfisyah; RR. Deni Widjayatri (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Marasmus is a form of malnutrition in which the amount of protein and calories consumed does not meet the body's needs, resulting in an energy deficit in the body. The purpose of this analysis is to analyze the causes of marasmus disease that occurs in early childhood so that readers can find out what symptoms if the child is affected by marasmus disease. The research method used is a literature review using bibliometric analysis of literature studies and the Publish or Perish application with Google Scholar as a data base. After narrowing the results by selecting a special topic on 'Causes of Marasmus Disease That Occurs in Early Childhood', 186 related articles were obtained for review from 1000 articles from the initial search results. Then the VOSViewer meta data application was used to visualize the research trend. The results showed that the classification of analysis on the Causes of Marasmus Disease That Occurs in Early Childhood was divided into 4 clusters. (green and red). Thus, our findings indicate that the main causes of marasmus in early childhood are malnutrition, infection, and environmental factors.